Pakistan : Export Diversification and Trade Policy - World Bank (Washington, DC, 2015)
Pakistan’s trade indicators reflect low outward orientation, concentration on low value added activities and an undiversified product mix which out of line with the fastest growing areas of world demand. The export share of Gross Domestic Product (GDP) has remained low and falling—fro